The burden of light work: the thought of Maria Ignez Silveira Paulilo on gender, labor, and rural women - Silveira Paulilo, Maria Ignez; Pillar Grossi, Miriam; Morelo Vergara Martins Costa, Suzana; de Araújo Nunes Esteves , Laura (Cadernos de Gênero e Diversidade, 2025)
The interview with Professor Maria Ignez Silveira Paulilo, conducted on November 23, 2022, in Florianópolis, is part of the NIGS/UFSC project on the contribution of women to the establishment of the Social Sciences program at UFSC. A nationally recognized scholar in rural women’s studies, Paulilo has built a long academic trajectory researching rural women’s labor and served as a professor at the Federal Universities of Campina Grande and Santa Catarina. In the interview, she revisits key moments of her career and analyzes both the political achievements of peasant women and the institutional advances in the inclusion of women within academia.